2019
DOI: 10.1159/000493893
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Literacy Support for Children from Marginalised Populations

Abstract: Background: The purpose of this paper is to describe the content and process of a literacy and language support model that was implemented with young children from marginalised communities, where no access to speech and language pathologist (SLP) services exists. The importance of language for literacy development is emphasised with explicit strategies for classroom application. Method: The SLP introduced an intervention programme to Early Childhood Development (ECD) kindergarten teachers, as part of a pre- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(41 reference statements)
0
7
0
1
Order By: Relevance
“…The intervention group children experienced an intervention where their teacher used more explicit instruction on skills relating to concepts about how print works and phonological awareness skills as opposed to the comparison group children within this particular time frame (see Table 4 ). Moonsamy and Carolus ( 2019 ) found, similarly, an increase in CAP scores at post-testing following a literacy intervention programme with South African ECD or preschool teachers. In this particular study, the researcher collaborated with teachers to promote explicit instruction on print concepts through varied reading strategies.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The intervention group children experienced an intervention where their teacher used more explicit instruction on skills relating to concepts about how print works and phonological awareness skills as opposed to the comparison group children within this particular time frame (see Table 4 ). Moonsamy and Carolus ( 2019 ) found, similarly, an increase in CAP scores at post-testing following a literacy intervention programme with South African ECD or preschool teachers. In this particular study, the researcher collaborated with teachers to promote explicit instruction on print concepts through varied reading strategies.…”
Section: Discussionmentioning
confidence: 77%
“…In this particular study, the researcher collaborated with teachers to promote explicit instruction on print concepts through varied reading strategies. Hence, Moonsamy and Carolus ( 2019 ) further promoted not only the need for explicit instruction but also the benefits of SLTs and teacher collaboration. Moonsamy and Carolus ( 2019 ) used storybooks as the resource for explicit instruction whilst Neumann et al ( 2013 ) and Vera ( 2007 ) found that CAP scores amongst their participants also increased at post-testing following environmental print interventions, specifically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children from SDCs are at risk for delay in language and literacy acquisition, which in turn will have a major impact on their future scholastic progress (Nel, Mohangi, Krog & Stephens, 2016). Access to support services is frequently absent; thus, language and literacy skills are compromised (Moonsamy & Carolus, 2019). Consequently, a vicious cycle of poor education, unemployment and poverty continues (Nel et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tasks are thus expected to be adapted to suit the South African population, and responses need to be interpreted with caution to avoid incorrect diagnoses. Thus, studies such as Tayob and Moonsamy (2018) and Moonsamy and Carolus (2019) are necessary, so that new avenues for assessment and intervention material can be explored. SLTs as agents of change have to be creative when working with children from SDCs and will not always be able to do individual interventions.…”
Section: Collaborative Approaches Of Slts and Teachers At Ecd Centresmentioning
confidence: 99%